Practical points on boat acceleration - Kleshnev, V. (BioRow, 2023)
Like many other biomechanical variables (e.g., force curve), the BA curve is a resultant indicator, and not a target itself and it is superfluous to attempt to "draw" a perfect curve directly. Instead, the focus should be on the rower`s technique: proper rhythm and timing at the catch (Catch Factor), synchronisation in a crew, body segment sequence (Rowing Style), gradients and coordination of stretcher-handle forces, etc. However, BA is a good indicator and may help to detect and improve technical problems, so here we will explain a few points of attention on the BA curve.